2011
DOI: 10.1017/s1461145711000691
|View full text |Cite
|
Sign up to set email alerts
|

Neuron density and serotonin receptor binding in prefrontal cortex in suicide

Abstract: Although serotonin receptor and cytoarchitectonic alterations are reported in prefrontal cortex (PFC) in suicide and depression, no study has considered binding relative to neuron density. Therefore, we measured neuron density and SERT, 5-HT1A and 5-HT2A binding in matched suicides and controls. Suicides and normal controls (N=15 matched pairs) were psychiatrically characterized. Neuron density and binding were determined in dorsal (BA9) and ventral (BA47) PFC by stereology and quantitative autoradiography in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 80 publications
9
60
1
2
Order By: Relevance
“…The reduction in 5-HT2A levels is also in concordance with another study comparing suicide versus non-suicide schizophrenia subjects using also Affymetrix microarrays, suggesting that this reduction in 5-HT2A levels might be involved in suicide irrespective of the diagnosis. We also observed decreased expression in suicide group of the brain specific ADCY1, a brain specific form of adenylate cyclase, suggesting altered neurotransmission and cyclic AMP signaling in suicide and confirms previous observations pointing to cAMP signaling alterations in suicide and mood disorders and in animal models of depression [136][137][138][139][140][141][142][143][144][145]. Both serotonergic alterations and second messenger systems underline global neurotransmission alterations in the DLPFC that seem to play a role in the predisposition to commit suicide [128].…”
Section: Genetic Criteriasupporting
confidence: 89%
“…The reduction in 5-HT2A levels is also in concordance with another study comparing suicide versus non-suicide schizophrenia subjects using also Affymetrix microarrays, suggesting that this reduction in 5-HT2A levels might be involved in suicide irrespective of the diagnosis. We also observed decreased expression in suicide group of the brain specific ADCY1, a brain specific form of adenylate cyclase, suggesting altered neurotransmission and cyclic AMP signaling in suicide and confirms previous observations pointing to cAMP signaling alterations in suicide and mood disorders and in animal models of depression [136][137][138][139][140][141][142][143][144][145]. Both serotonergic alterations and second messenger systems underline global neurotransmission alterations in the DLPFC that seem to play a role in the predisposition to commit suicide [128].…”
Section: Genetic Criteriasupporting
confidence: 89%
“…Consistent with this, 5-HT 1A autoreceptor levels negatively correlate with levels of the plasmalemmal 5-HT transporter (SERT) in PET studies [137,138], and in post-mortem studies [108,139]. Interestingly, increased 5-HT 1A autoreceptor binding is associated with reduced response to antidepressants [102,140], which could reflect greater autoreceptor-mediated inhibition of 5-HT.…”
Section: Association Of Rs6295 With Altered 5-ht 1a Receptor Expressimentioning
confidence: 59%
“…34 Moreover, postmortem studies have consis tently shown neurochemical evidence of serotonergic hypo function in victims of suicide. [35][36][37] We hypothesized that de pressed individuals would display an inflammatory profile characterized by increased cytokine expression that would correlate with increased KP activity. Results of the present study did not confirm our assumptions.…”
Section: Introductionmentioning
confidence: 99%